Experimental Investigation of Pressure Fluctuation, Vibration, and Noise in a Multistage Pump - Kai Wang; Zixu Zhang; Chen Xia; Zhongchun Liu (Shock and Vibration)
In order to measure the pressure pulsation, vibration, and noise characteristics of multistage centrifugal pump in different flow rates, a five-stage centrifugal pump was chosen as research object. The results show that the main frequency of pressure pulsation was BPF1, 9APF, BPF2, BPF2, and 9APF. According to the order of monitoring points, the intensity of the pressure fluctuation increased and then decreased, with the strongest fluctuation at monitoring point P2. The peak value of pressure fluctuation in monitoring point P2 was obviously higher than the other monitoring points. The main characteristic frequency of vibration is 4APF, BPF2, 9APF, 2BPF2, 3BPF1, 4BPF1, and 4BPF2. The number of characteristic frequencies at the outlet flange was significantly more than the number of characteristic frequencies at the inlet flange. As the flow rate increased, the vibration of motor gradually increased and the vibration of pump increased at first and then decreased. It reached the minimum vibration level in the design flow rate. Motor contributed the largest amount of noise caused by the pump unit. The noise level of measure point which is close to motor is higher than that of other measure points. As the flow rate increased, the noise incrementally increased, and the difference in noise level between measure points decreased gradationally. When the flow rate was 120 m3/h, the maximum difference value of different noise monitoring points was only 1.7 dB.